Longitudinal Change in Disability and Functioning in Patients With Moderate-to-Severe Parkinson’s Disease: A Population-Based Assessment Using the World Health Organization Disability Assessment Schedule 2.0 - Hsun-Hua Lee; Lung Chan; Wen-Chou Chi; Chia-Feng Yen; Hua-Fang Liao; Tsan-Hon Liou; Chien-Tai Hong (Asia Pacific Journal of Public Health, 2026)
Parkinson’s disease (PD) is associated with progressive disability and declining functioning, yet longitudinal population-based evidence using standardized assessments remains limited. Using the Taiwan Databank of Persons with Disabilities, we identified patients with moderate-to-severe PD (Hoehn and Yahr stages III-V) who underwent baseline and follow-up World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0) assessments within 1 to 5 years. Longitudinal changes were evaluated using repeated-measures analysis of covariance, and multivariable logistic regression identified factors associated with rapid progression, defined as an annual increase of at least 2 points. Among 2281 patients (mean follow-up, 2.9 ± 1.2 years), disability and functioning worsened significantly over time ( P < .001), with an average annual increase of 1.87 points. Declines occurred across all domains except participation, with the greatest deterioration in getting along and cognition. Significant interactions were observed between age and cognition and between dementia status and mobility, self-care, and life activities. Rapid progression was independently associated with age ≥65 years (adjusted odds ratio [aOR] 1.776, 95% confidence interval [CI] 1.416-2.228) and dementia progression (aOR 1.826, 95% CI 1.345-2.478). These findings highlight substantial longitudinal deterioration in disability and functioning in moderate-to-severe PD, particularly in cognition, and support the importance of early functional assessment and identification of patients at high risk of rapid progression.